Osteomyelitis of the mandible in the patient with plasmocytoma - case report - Wioletta Anna Bal; Tomasz Krzysztof Bąk; Beata Krasuska; Weronika Sandra Topyła; Jolanta Elżbieta Wojciechowicz (Kazimierz Wielki University, 2017)
Osteomyelitis is an infection of bone which may be caused by infection carried to the bone via the bloodstream or from surrounding tissue. Treatment of osteomyelitis of the mandible is extremely difficult because of oral environment and teeth presence. Management often involves both debridement and antibiotic selection. Despite this, aggressive surgical interventions and conservative therapy are most important aspects of treatment. Medication-related osteonecrosis of the jaw (MRONJ) is an avascular necrosis related to osteomyelitis and characterized by necrotic bone in the maxillofacial region. The prevalence of this is associated with treatment with high-potency bisphosphonates or denosumab and it seems to be getting increasingly frequent. Due to lack of prospective studies with long-term follow-up there are no recommendation for treatment of MRNOJ. The main aim of treatment of patients with MRNOJ is to continue and to support oncological treatment as well as to provide patient education, comfort to life, control of pain and to prevent from secondary infection and development of new areas of necrosis.